The Evolutionary Conserved SWI/SNF Subunits ARID1A and ARID1B Are Key Modulators of Pluripotency and Cell-Fate Determination - Pagliaroli, Luca; Trizzino, Marco (Frontiers in Cell and Developmental Biology, 2021)
Organismal development is a process that requires a fine-tuned control of cell fate and identity, through timely regulation of lineage-specific genes. These processes are mediated by the concerted action of transcription factors and protein complexes that orchestrate the interaction between cis-regulatory elements (enhancers, promoters) and RNA Polymerase II to elicit transcription. A proper understanding of these dynamics is essential to elucidate the mechanisms underlying developmental diseases. Many developmental disorders characterized by growth impairment and intellectual disability are associated with mutations in subunits of the SWI/SNF chromatin remodeler complex, which is an essential regulator of transcription. For example, ~70% of the patients affected by Coffin-Siris Syndrome, a congenital disease whose phenotype includes defects in the physical development and intellectual disability, present with mutations in ARID1B. This gene and its paralog ARID1A encode for the two largest, mutually exclusive, subunits the of complex. Mutations in ARID1A and, especially, ARID1B have been recurrently associated with a very wide array of developmental disorders, suggesting that the these two SWI/SNF subunits play an important role in cell fate decision. In this mini-review we therefore discuss the available scientific literature linking ARID1A and ARID1B to cell fate determination, pluripotency maintenance, and organismal development.